Regulatory role of the lncRNAs MIAT and PVT1 in Behçet's disease through targeting miR-93-5p and miR-124-3p - Asmaa A. ElMonier; Olfat G. Shaker; Shimaa O. Ali (BMC, 2024)
Abstract Background Noncoding RNAs play pivotal roles in the process of autoimmune diseases. However, the definite contributions of these molecules to Behçet's disease (BD) are still unknown. This study aimed to explore the clinical value of a novel competing endogenous (ce) RNA network in the pathogenesis of BD and to assess its use in primary diagnosis. Methods Bioinformatic analysis was applied to construct a BD-related ceRNA network: lncRNA (MIAT and PVT1)-miRNA (miR-93-5p and miR-124-3p)-mRNA (SOD-2 and MICA). Blood was obtained from 70 BD patients and 30 healthy subjects, and the serum expression of the tested RNAs was estimated via quantitative real-time PCR (qPCR). Serum tumor necrosis factor-alpha (TNF-α) levels were also determined. The associations between these RNAs were further analyzed, and receiver operating characteristic (ROC) curve and logistic regression analyses were employed to validate their diagnostic and prognostic values. Results The expression levels of the lncRNAs PVT1 and miR-93-5p were significantly increased, whereas those of the lncRNAs MIAT and miR-124-3p, as well as those of the SOD-2 and MICA mRNAs, were significantly decreased in BD patients compared with controls. BD patients had significantly higher serum TNF-α levels than controls did. ROC curve analysis indicated that the selected RNAs could be candidate diagnostic biomarkers for BD. Moreover, the highest diagnostic efficiency was achieved with the combination of MIAT and miR-93-5p or PVT1 and miR-124-3p with either SOD-2 or MICA. Logistic regression analysis revealed that all RNA expression levels could be predictors for BD. Conclusion Mechanistically, our research revealed a novel ceRNA network that is significantly disrupted in BD. The findings reported herein, highlight the noncoding RNA-molecular pathways underlying BD and identify potential targets for therapeutic intervention. These insights will likely be applicable for developing new strategies for the early diagnosis, management and risk assessment of BD as well as the design of novel preventive measures. Trial registration The protocol for the clinical studies was approved by Cairo University's Faculty of Pharmacy's Research Ethics Committee (approval number: BC 3590)